Conceptions and reactions to mental illness by the public of Dumaguete City - Pontenila, Emma Merced B.
Mental illness is a fast-growing problem in the Philippines, as well as in other countries. Yet many people do not know much about mental illness. And, as researchers have observed, they hold either traditional or modern view on mental illness, or have positive or negative attitudes towards it. This study was undertaken to verify current research findings, to determine the extent and nature of mental illness, and to establish baseline data for the promotion of health and improvement of health care delivery. This study explores the public conceptions on attitudes towards, and reactions to mental illness, as well as the public's knowledge on available mental health services and issues related to mental health. For this study, 160 urban and rural households of Dumaguete City were randomly selected in clusters. Each household's decision-maker was interviewed and responses were measured with the use of a Likert scale. This study shows that the public sees the mentally ill person as sloppy-looking, addicted to drugs, nervous and speaker of a strange language. Prognosis of mental illness is viewed both positively and negatively by the public. In this study, the public's conceptions of the causes of mental illness are varied-physical, environmental, hereditary, interpersonal, psychological, and to a lesser degree, supernatural. Education was found to be the strongest predictor of the public's conceptions and reactions to mental illness. It is encouraging to note that in this study, the public's attitude tended to be positive. And whatever stigma attached to mental illness is due mainly to people's belief that mentally ill persons are dangerously unpredictable. Rejection of those who have recovered from mental illness is limited. That is, people are reluctant to accept as boarders or hire former mental patients. This study also shows that the majority of the public are aware of mental health services in their own community but not many people know these services are available in neighboring areas.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Mental illness -- Public opinion; Mental illness